LINFADENITE INFECCIOSA EM SUÍNOS: ETIOLOGIA, EPIDEMIOLOGIA E ASPECTOS EM SAÚDE PÚBLICA - Lara, G.h.b [UNESP]; Ribeiro, M.g. [UNESP]; Guazzelli, A. [UNESP]; Fernandes, M.c. [UNESP] (Instituto Biológico, 2021)
Infectious lymphadenitis in swine leads to high damages with losses of carcasses, due to similarity of lesions caused by causal agents and zoonotic risks of certain microorganisms, reinforcing the importance of periodic sanitary vigilance in affections of lymph nodes in swine. The increased occurrence of Mycobacterium sp. and Rhodococcus equi in patients affected by acquired immunodeficiency syndrome (AIDS) has underscored the importance of the monitoring of infectious lymphadenitis in slaughterhouses, as these microorganisms are among the most common causes of swine lymphadenitis. The present article reviewed the main aspects of lymphadenitis in swine, with emphasis on the epidemiology and public health impact, and Mycobacterium and Rhodococcus equi as causal agents.

A linfadenite infecciosa em suínos gera altos prejuízos com a condenação de carcaças, pela similaridade das lesões causadas pelos agentes causais e de certos micro-organismos, reforçando a necessidade da vigilância sanitária continuada nas afecções de linfonodos em suínos. O crescente isolamento de Mycobacterium sp. e de Rhodococcus equi em pacientes acometidos pela síndrome da imunodeficiência adquirida (Aids) redobrou a preocupação na vigilância da linfadenite na linha de abate, em virtude destes micro-organismos figurarem dentre as principais causas da linfadenite em suínos. O presente artigo revisou os principais aspectos da linfadenite infecciosa em suínos, com ênfase na epidemiologia e reflexos em saúde pública, e a ocorrência de Mycobacterium sp. e R. equi como agentes causais da linfadenite.
INFECTIOUS LYMPHADENITIS IN SWINE: ETIOLOGY, EPIDEMIOLOGY AND PUBLICHEALTH ASPECTS
Keywords: Swine; Mycobacterium; R. equi; Suínos; Mycobacterium; Rhodococcus equi